Creating Space for Visual Ethnography in Educational Research - Barrantes-Elizondo, Lena (2019)
This article maps the territory of visual ethnography as a key and accessible research methodology in education. It aims to provide an overview and to present theory and practice for future research. The origins and principles of visual ethnography are disclosed as well as some methods to gather data. From the premise that either created by the researcher, by the participants, or through collaboration between both, images may be the core of analysis of social and cultural views and perceptions of students, educators, administrators and community members. The author addresses ethical issues like confidentiality, and highlights possible biases like authenticity, negotiated construction, trustworthiness, and deception of information. The main conclusions highlighted the importance of visual ethnography as a key methodology to elicit rich data that access students’ voices, the space for participatory techniques, and the role of technology as an undeniable participant.